2005
DOI: 10.1007/s00415-005-0594-5
|View full text |Cite
|
Sign up to set email alerts
|

Posterior cortical atrophy: variant of Alzheimer?s disease?

Abstract: Nine patients with posterior cortical atrophy (PCA), a rare degenerative brain disease of unclear etiology and nosology, were followed over a mean time of 7.4 years. The mean age at onset was low (56.2 years). At onset, eight patients had visuo-spatial and eight had memory impairment. A minority showed early signs of occipital lobe involvement with visual agnosia or hemianopia. Eight patients developed dementia after a mean course of five years. 18F-FDG-PET data of six patients were analysed with statistical p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
33
0
5

Year Published

2006
2006
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(43 citation statements)
references
References 31 publications
5
33
0
5
Order By: Relevance
“…Selective deficits in dorsal pathways have previously been demonstrated using volume measurements [8], PET [47] and SPECT [48]. Since the BOLD fMRI signal is known to be influenced by cortical atrophy, metabolism and blood flow, our data support and add to the existing literature.…”
Section: Discussionsupporting
confidence: 87%
“…Selective deficits in dorsal pathways have previously been demonstrated using volume measurements [8], PET [47] and SPECT [48]. Since the BOLD fMRI signal is known to be influenced by cortical atrophy, metabolism and blood flow, our data support and add to the existing literature.…”
Section: Discussionsupporting
confidence: 87%
“…Homonymous hemianopia may also be present [5]. Magnetic resonance imaging (MRI) usually shows cortical atrophy in the parietal, occipital and posterior temporal regions [6], while [ 18 F]fluorodeoxyglucose positron emission tomography (FDG-PET) may reveal hypometabolism in the posterior cerebral hemispheres, even in the absence of concomitant atrophy [7,8]. This syndrome almost universally progresses to more diffuse cognitive impairment and dementia.…”
Section: Introductionmentioning
confidence: 99%
“…Consistent with their clinical presentation, patients with PCA show gray matter (GM) loss in parieto-occipital and posterior temporal cortices, which is often more prominent in the right hemisphere (Galton et al, 2000; Whitwell et al, 2007). Positron emission topography (PET) studies have reported a prominent hypometabolism in the same posterior brain areas (Nestor et al, 2003; Schmidtke et al, 2005; Bokde et al, 2005). Although PCA patients do not meet clinical criteria for Alzheimer’s disease (AD), because of the lack of memory impairment as core of the syndrome, pathological series have found that the majority of PCA patients have senile plaques and neurofibrillary tangles, both hallmarks of AD, at autopsy (von Gunten et al, 2006; Renner et al, 2004; Tang-Wai et al, 2004; Alladi et al, 2007).…”
Section: Introductionmentioning
confidence: 99%